MICROSCOPIC CHANGES IN THE INTERNAL ORGANS OF WHITE MICE DURING EXPERIMENTAL IRON (IV) CLATHROCHELATE TOXICOSISS - B. V. Borysevich; Viktoriia Lisova; I. M. DERKACH; Serhii Derkach; V. B. Dukhnitskyi; A. M. TYSHKIVSKA (Ukrainian Journal of Veterinary Sciences, 2021)
Iron (IV) clathrochelate based on a macrobicyclic ligand of the hexahydrazide type is a unique compound that contains iron in a rare high valence IV. Preclinical and clinical studies of this complex, which were started for the first time in Ukraine, have an important theoretical and practical consequence as this complex can be recommended as an active substance in iron-containing drugs with antianemic action. In conducting preclinical studies of new drugs, pathomorphological studies are important because they are a necessary step in studying the biological response of animals to the action of test substances. It was found that some pathological changes develop in the body of white mice under conditions of experimental acute and chronic iron (IV) clathrochelate intoxication. They correlated with the dose of the test compound. During chronic intoxication, the microscopic changes in the liver and kidney of white mice treated with iron (IV) clathrochelate at a dose of 1/10 DL50 were similar to the microscopic changes in the liver and kidney of mice treated with the experimental drug at a dose of 1/5 DL50. However, the severity of these changes was lower, reflecting a lower degree of organ damage. In the myocardium of mice treated with iron (IV) clathrochelate at a dose of 1/5 DL50, as during acute iron (IV) clathrochelate poisoning, only edema was recorded on the 10th day. The prospects for further research are the study of microscopic changes in the organs of laboratory animals of other species during experimental iron (IV) clathrochelate toxicosis